PENDAMPINGAN GROWTH MINDSET DALAM PENDAMPINGAN PENERAPAN DISIPLIN POSITIF BAGI USTADZ/USTADZAH - Jamhuri, M.; Yusuf, Achmad (Jurnal Abdi Insani, 2025)
Islamic boarding schools (pesantren) play a strategic role in shaping the character and morals of the younger generation, while also serving as crucial institutions for fostering morals and religious knowledge. They aim not only to educate students academically but also to cultivate noble personalities.This community service program aims to improve the competitiveness and performance of creative SMEs affiliated with the Nahdlatul Ulama Young Entrepreneurs Association (HPMNU) in Pasuruan Regency. The main challenges faced by partners are suboptimal supply chain management, minimal innovation, and low utilization of digital technology for marketing. Community service activities include intensive training and mentoring in supply chain integration, innovation capacity development, and digital marketing adoption. The method used is a participatory approach with stages of needs identification, training implementation, and outcome evaluation. Results show that partners have improved skills in managing supply chains, designing product innovation strategies, and using digital platforms to expand markets. The tangible impact of this program includes increased operational efficiency, product creativity, and broader market access.